Elite-Mass Linkages in the Preference Formation on Differentiated Integration - de Vries, Catherine; Telle, Stefan; Cicchi, Lorenzo (Wiley, 2022)
How does the public form preferences about differentiated integration (DI)? The literature on mass-elite linkages offers two perspectives: top-down, political elites cue the public, or bottom-up, political elites react to public preferences. This paper develops expectations based on both perspectives, and presents novel empirical data on citizens, political parties, and governments to test them. We distinguish preferences over differentiated policy integration, like ‘Opt-Outs’, from preferences over polity differentiation, such as ‘Two-Speed Europe’. Although our evidence is observational and therefore cannot establish causal relationships between elites and the mass public, our results are most compatible with the notion of a top-down linkage. This is because DI preferences are generally of low salience, and first revealed at the European level in the context of negotiations. Subsequently, this revelation of DI preferences shapes domestic discussions about DI, especially at the level of political parties. Yet, this mostly pertains to situations when governments do not yet have clear DI preferences of their own, meaning government preferences are not yet formed and revealed in the context of the supranational negotiations. Overall, this study suggests that mass-elite linkage in the preference formation on DI might be more tenuous than either the top-down or bottom-up perspective might assume.
Keywords: European Union; differentiated integration; preference formation; mass-elite linkages; 59 Ciencia Política; ODS 10 - Reducción de las desigualdades